Preserved SARS-CoV-2 Vaccine Cell-Mediated Immunogenicity in Patients With Inflammatory Bowel Disease on Immune-Modulating Therapies. Issue 4 (28th April 2022) - Boland, Brigid S.; Goodwin, Benjamin; Zhang, Zeli; Bloom, Nathaniel; Kato, Yu; Neill, Jennifer; Le, Helen; Tysl, Tiffani; Collins, Angelina E.; Dulai, Parambir S.; Singh, Siddharth; Nguyen, Nghia H.; et al.
Abstract : Immune-modulating medications for inflammatory bowel diseases (IBDs) have been associated with suboptimal vaccine responses. There are conflicting data with SARS-CoV-2 vaccination. We therefore assessed SARS-CoV-2 vaccine immunogenicity at 2 weeks after second mRNA vaccination in 29 patients with IBD compared with 12 normal healthy donors. We observed reduced humoral immunity in patients with IBD on infliximab. However, we observed no difference in humoral and cell-mediated immunity in patients with IBD on infliximab with a thiopurine or vedolizumab compared with normal healthy donors. This is the first study to demonstrate comparable cell-mediated immunity with SARS-CoV-2 vaccination in patients with IBD treated with different immune-modulating medications.